Bahasa Indonesia Implikasi Model Sistem Ilmu Pendidikan Islam di Indonesia: Sistem Pendidikan Islam dan Nasional - Nurulfitri, Nabilah; Khairunnisa, Anzani; Nadiroh, Nadiroh; Muhajir, Muhajir (Ri'ayah: Jurnal Sosial dan Keagamaan, 2024)
The implications of the educational system model certainly have diversity both in education in general and in religions that have spread throughout Indonesia. The aim of this research is a form of awareness in improving the education system in Indonesia, especially in the field of Islamic religious education. This type of research uses a literature review that uses books, articles and other reading support sources. Islamic education does not only focus on religious aspects, but also includes aspects of morals, morality and the development of students' potential as a whole. The goals of Islamic education include the formation of noble morals, preparation for life in this world and the afterlife, seeking beneficial sustenance, cultivating a scientific spirit, and providing lessons in various professional fields.